Victory disc - Cartmel, Andrew (Cartmel, Andrew. Vinyl detective, 2020)
"This time the search for a rare record ensnares our hero in a mystery with its roots stretching back to the Second World War. Three young RAF airmen played in a legendary band called the Flare Path Orchestra. When a precious record of their music turns up in the most unexpected place, the Vinyl Detective finds himself hired to track down the rest of their highly sought-after recordings. But, as he does so, he finds that the battles of the last World War aren't over yet--and can still prove lethal"--